2002
DOI: 10.1051/rnd:2002010
|View full text |Cite
|
Sign up to set email alerts
|

Increasing amounts of dietary myristic acid modify the plasma cholesterol level and hepatic mass of Scavenger receptor BI without affecting bile acid biosynthesis in hamsters

Abstract: -The purpose of this study was to analyze the effects of increasing amounts of dietary myristic acid (0.03 to 4.2% of the total dietary energy) on the plasma and hepatic cholesterol metabolism. Six groups of hamsters received semi-purified diets containing 0.05% cholesterol and 12.5% lipids and differing only by the nature of the triglycerides (Safflower oil, lard, lard/coconut oil (1:1), milk fat, milk fat/coconut oil (1:1), coconut oil) for 3 weeks. A positive regression between the plasma cholesterol level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
1
11
0
3
Order By: Relevance
“…Moreover, we observed that the level of dietary cholesterol had no effect on the lipid values in the plasma and liver. This result was in accordance with a recent study showing that, in the hamster, an increase in the level of plasma HDL-cholesterol resulting in a slight and not significant increase in plasma total cholesterol concentration, was related to the amount of C14:0 (0.5 to 2.4%) in the diet [9,10]. By studying the tissue FA compositions of the rats (Tabs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, we observed that the level of dietary cholesterol had no effect on the lipid values in the plasma and liver. This result was in accordance with a recent study showing that, in the hamster, an increase in the level of plasma HDL-cholesterol resulting in a slight and not significant increase in plasma total cholesterol concentration, was related to the amount of C14:0 (0.5 to 2.4%) in the diet [9,10]. By studying the tissue FA compositions of the rats (Tabs.…”
Section: Discussionsupporting
confidence: 92%
“…It corresponds to 4-8 g.day -1 i.e., 0.5 to 2.0% of total energy, coming essentially from dairy fat [8]. At these physiological levels (0.5 to 2.4% of total dietary energy), recent studies analyzing the effects of increasing doses of dietary myristic acid in hamsters showed a small increase in plasma total cholesterol that only reflected an increase in the level of high density lipoprotein (HDL)-cholesterol and not in the level of LDL-cholesterol [9,10]. In young men, meals rich in myristic acid also result in a higher HDL-cholesterol concentration within 24 h than meals rich in stearic acid, without affecting the other lipoprotein parameters [11].…”
Section: Introductionmentioning
confidence: 99%
“…We first investigated the incorporation into lipids and the β-oxidation rate of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]-lauric acid. Although lauric acid was rapidly taken up by the cells (95% of the precursor was cleared from the medium after 4 h), the 14 C incorporation into total cellular fatty acids was low after 4 h incubation, representing only 24% of the initial radioactivity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This increase seems to be largely explained by a decrease in hepatic LDL receptor activity [11,12] and an increase in LDL-cholesterol production rate. A recent study analyzing the effects of increasing amounts of dietary myristic acid in hamsters showed, however, that the increase in total plasma cholesterol only reflects an increase in the level of HDL-cholesterol [13]. New mechanisms involving exogenous lauric acid have also recently been shown to induce the expression of genes through the modulation of Toll-like receptor 4 in macrophages [14].…”
Section: Introductionmentioning
confidence: 99%
“…Il est utilisé en cosmétique et en industrie pharmaceutique (MERCK, 1996). Consommé à dose physiologique, l'acide myristique aurait un effet favorable sur le profil lipidique comme le montre une étude réalisée chez le hamster (LOISON et al, 2002). Récemment, il a été également identifié parmi les acides gras responsables des arômes de distillation de l'extrait des prunes (TESEVIC et al, 2005).…”
Section: Parmi Les Métabolites Identifiés Nous Citonsunclassified